2019
DOI: 10.1017/s1478951519000920
|View full text |Cite
|
Sign up to set email alerts
|

Impact of enucleation on adult retinoblastoma survivors’ quality of life: A qualitative study of survivors' perspectives

Abstract: AbstractObjectivesRetinoblastoma is the most common primary intraocular tumor of childhood with >95% survival rates in the US. Traditional therapy for retinoblastoma often included enucleation (removal of the eye). While much is known about the visual, physical, and cognitive ramifications of enucleation, data are lacking about survivors' perception of how this treatment impacts overall quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 34 publications
(54 reference statements)
3
17
0
Order By: Relevance
“…Perhaps cases with systemic malignancies might have died and were not reported in the registry resulting in the high score for the physical health subgroup. Our outcomes concur with Banerjee et al’s 10 who noted lower levels of positive attitude for future and suggested teaching the patients coping strategies to develop a positive attitude and increase HQL. A Danish study reported higher divorce rates and related stress among individuals who had undergone bilateral enucleation.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Perhaps cases with systemic malignancies might have died and were not reported in the registry resulting in the high score for the physical health subgroup. Our outcomes concur with Banerjee et al’s 10 who noted lower levels of positive attitude for future and suggested teaching the patients coping strategies to develop a positive attitude and increase HQL. A Danish study reported higher divorce rates and related stress among individuals who had undergone bilateral enucleation.…”
Section: Discussionsupporting
confidence: 92%
“…The high HQL score noted the current study differs from the HQL reported in other studies. 6,9,10 This could be due to the different assessment tools used to determine HQL. Banerjee et al 10 had assessed both unilateral and bilateral removal of the globe to treat Rb.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations